Adherence to "What Works": Examining Trends across 14 Years of Correctional Program Assessment. Issue 4 (8th August 2021) - Farringer, Alison J.; Duriez, Stephanie A.; Manchak, Sarah M.; Sullivan, Carrie C.
ABSTRACT: The "what works" movement has increasingly gained recognition among correctional practitioners and traction within correctional settings. It is now well established that in order to obtain meaningful recidivism reductions, programs must maintain fidelity to the principles of effective interventions. After more than four decades of research supporting the Risk-Need-Responsivity model, little is presently known about how well correctional programs have adopted and implemented evidence-based correctional practices on a larger scale. The current study examines the results from an extensive collection of correctional program assessments completed across the United States over the course of 14 years. Results offer practitioners and researchers insight into the current state of fidelity to evidence-based practices and highlight areas for improvement in correctional programming.